Hak menguasai negara merupakan prinsip dasar kewenangan negara dalam pemilikan dan penguasaan tanah (kajian Hak Pakai Khusus Atas Tanah) - Bur, Arifin (Universitas Islam Riau Indonesia, 2010)
Since the Independence of the Republic of Indonesia on 17th August 1945, the Constitution of 1945 has become the highest written law in Indonesia. In Land law, the Act of No. 5 of 1960 (hereinafter is called UUPA) is applicable governing the land matters and agrarian reform. According to article 33 (2) of the 1945 Constitution the State has power to determine the right to control property, including the land. Besides, Article 2 of the UUPA stipulates the basic rules as to the relationship between the State power and the right holder of the land. Accordingly, the State recognizes the ownership of the land by an individual or by private legal entity and by public legal body in terms of right to use for the government body. The implementation of the power of the State to confer the right on land as property is mentioned in Article 16 UUPA namely the right of the land permanently or temporarily, and other rights as determined by the law in future. The right to use of land is not covered by Article 16 UUPA, but shall be governed by law. As far as the special right to land use is concerned it is laid down under Articles 41 and Article 42 and also in general explanation II/2 UUPA. It is therefore suggested that the State Authority should enact the Act to determine such right on grounds : firstly it is possible for the government to do so on the basis article 16 UUPA strictly but then the implementation of Article 16 UUPA has become unlimited. Secondly, there exists the vast power of the state, and thirdly, the legislations in Indonesia confers vast and unlimited power to State to control the land which might lead to the abuse of power by the State. The special right to use of land should cover many factors, namely : the right, content of right, the burden of land towards the other right of land, subject of right, and land as the object of right. While factors embodied in right of control of land consist of : ownership, transfer or right to other(s), deletion of right, and the proof of right. Therefore it is suggested that the government should enact the law to lay down the special right to use of land in near future